2010
DOI: 10.1194/jlr.m003061
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective epoxidation of the last double bond of polyunsaturated fatty acids by human cytochromes P450

Abstract: family 1 to 3 are mainly epoxygenases, whereas CYP isoforms from family 4 are mainly -hydroxylases ( 4, 5 ).CYP epoxygenases convert arachidonic acid (AA) to four epoxyeicosatrienoic acid regioisomers (5,8,11,and 14, that function as lipid mediators. EETs produce vascular relaxation, have antiinfl ammatory effects on blood vessels and in the kidney, promote angiogenesis, and protect ischemic myocardium and brain [for review, see ( 6-8 )]. CYP epoxygenases also convert the 3-PUFA eicosapentaenoic acid (EPA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 38 publications
(56 reference statements)
9
58
0
Order By: Relevance
“…Additionally, the vasoprotective benefits of n-3 PUFAs may be enhanced further by TCDD, since TCDD significantly increases levels of 17,and 10,16,[17][18][19]20-EDP in the liver and plasma. The increases in 17,18-EEQ and 19,20-EDP likely result from induction of CYP1A1 and 1A2, since recombinant enzyme studies of CYP1A1 and 1A2 show that they generate these 2 epoxides with high efficiency and stereospecificity (Fer et al, 2008;Lucas et al, 2010;Schwarz et al, 2004). The P450s responsible for the increases of 10,11-and 16,17-EDP by TCDD are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the vasoprotective benefits of n-3 PUFAs may be enhanced further by TCDD, since TCDD significantly increases levels of 17,and 10,16,[17][18][19]20-EDP in the liver and plasma. The increases in 17,18-EEQ and 19,20-EDP likely result from induction of CYP1A1 and 1A2, since recombinant enzyme studies of CYP1A1 and 1A2 show that they generate these 2 epoxides with high efficiency and stereospecificity (Fer et al, 2008;Lucas et al, 2010;Schwarz et al, 2004). The P450s responsible for the increases of 10,11-and 16,17-EDP by TCDD are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…5,6-Oxidosqualene and 10,11-oxidosqualene are not observed in the reaction catalyzed by SE (van Duuren and Schmitt , 1960 ;Abe et al , 2007 ). Oxidation of the terminal double bonds is characteristic for other enzymatic reactions (Lucas et al , 2010 ). Zeaxanthin epoxidase oxidizes double bonds only at the ends of zeaxantin, despite the fact that this substrate, like squalene, contains several internal double bonds which could be potentially epoxidized (Hieber et al , 2000 ).…”
Section: Specifi City Of Epoxidation Reactionmentioning
confidence: 99%
“…www.intechopen.com (Fer et al, 2008, Arnold et al, 2010, Lucas et al, 2010. Several epoxygenases have been identified in lung tissues, including 2J2, 2C8 2C9 and 1B1 (Fer et al, 2008).…”
Section: Key Role Of Cyp450 Epoxygenase-dependent Metabolites Derivedmentioning
confidence: 99%
“…Epoxy-docosapentaenoic acids are CYP450-dependent DHA metabolites (Fig. 1C) (Fer et al, 2004, Arnold et al, 2010, Lucas et al, 2010 and recent studies have demonstrated that these metabolites display potent vasodilatory activities on coronary arteries (Konkel et al, 2011, Wang et al, 2011. Metabolic pathways and chemical structures of CYP450-dependent AA, EPA and DHA metabolites known to modulate vascular tone are illustrated in Figure 1 A-C.…”
Section: Introductionmentioning
confidence: 99%